2015
DOI: 10.1111/cdev.12463
|View full text |Cite
|
Sign up to set email alerts
|

Affecting Girls’ Activity and Job Interests Through Play: The Moderating Roles of Personal Gender Salience and Game Characteristics

Abstract: Gender schema theory (GST) posits that children approach opportunities perceived as gender appropriate, avoiding those deemed gender inappropriate, in turn affecting gender-differentiated career trajectories. To test the hypothesis that children's gender salience filters (GSF-tendency to attend to gender) moderate these processes, 62 preschool girls (M = 4.5 years) were given GSF measures. Two weeks later, they played a computer game about occupations that manipulated the game-character's femininity (hyperfemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 54 publications
2
35
1
Order By: Relevance
“…For the attitudinal pathway model, research supports the distinction in schematicity, finding within-gender differences in toy, activity, and occupation preferences between genderschematic and gender-aschematic children (Carter and Levy 1988;Coyle and Liben 2016;Lobel and Menashri 1993, in Isreal;Martin and Dinella 2012;Patterson 2012;WilanskyTraynor and Lobel 2008, in Isreal). Although much research has been conducted using assessments of gender-typed interests and gender attitudes about culturally stereotyped activities, occupations, and behaviors (Liben and Bigler 2002;Signorella and Frieze 2008), research with novel items is necessary to disentangle the cultural stereotypes of an item from the properties of the item itself.…”
Section: Dual Pathway Model Of Gender Differentiationmentioning
confidence: 90%
See 1 more Smart Citation
“…For the attitudinal pathway model, research supports the distinction in schematicity, finding within-gender differences in toy, activity, and occupation preferences between genderschematic and gender-aschematic children (Carter and Levy 1988;Coyle and Liben 2016;Lobel and Menashri 1993, in Isreal;Martin and Dinella 2012;Patterson 2012;WilanskyTraynor and Lobel 2008, in Isreal). Although much research has been conducted using assessments of gender-typed interests and gender attitudes about culturally stereotyped activities, occupations, and behaviors (Liben and Bigler 2002;Signorella and Frieze 2008), research with novel items is necessary to disentangle the cultural stereotypes of an item from the properties of the item itself.…”
Section: Dual Pathway Model Of Gender Differentiationmentioning
confidence: 90%
“…These models are considered constructivist because children are actively, cognitively constructing stereotypes through interaction with their environment (Coyle and Liben 2016;Liben and Bigler 2002). Prominent constructivist models of gender stereotyping include social cognitive theory (Bussey and Bandura 1999), cognitive developmental theory (Kohlberg 1966), and gender schema theory (Bem 1981;Martin and Halverson 1981).…”
Section: Constructivist Perspectives On Gender Stereotypesmentioning
confidence: 99%
“…Empirical findings have demonstrated the value of studying effects of individual differences and dual pathways. For example, as discussed in greater detail later, findings from an experimental study (Coyle & Liben, in press) showed that under some conditions, preschool girls respond differently to a game about occupations in relation to individual differences in their general attentiveness to gender. Findings from a longitudinal study (Liben & Bigler, ) showed support for the hypothesized impact of the personal (self‐to‐other) pathway: Middle school boys who initially (fall of Grade 6) selected more feminine descriptors as self‐descriptive later (spring of Grade 7) reported more egalitarian gender attitudes about others.…”
Section: Gender‐differentiating Processesmentioning
confidence: 99%
“…Second, and as argued in greater detail elsewhere (see Liben, ; Liben & Coyle, ), it is also crucial to test for unintended consequences, or what I have more provocatively referred to as collateral damage (Liben, ). One can well imagine that there would be unintended lessons about what it means to be a woman when the models who tout science are women who might be labeled in scholarly terminology as “hyperfeminized” (Coyle & Liben, in press) or in common parlance as “sexy.” What will men who watch the Science: It's a Girl Thing! video think about the contributions women colleagues will make to collaborative projects?…”
Section: Gender‐relevant Interventionsmentioning
confidence: 99%
See 1 more Smart Citation